Customer perceived service quality, satisfaction and loyalty in Indian private healthcare. Issue 5 (8th June 2015) - Kondasani, Rama Koteswara Rao; Panda, Rajeev Kumar
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to analyse how perceived service quality and customer satisfaction lead to loyalty towards healthcare service providers. Design/methodology/approach – In total, 475 hospital patients participated in a questionnaire survey in five Indian private hospitals. Descriptive statistics, factor analysis, regression and correlation statistics were employed to analyse customer perceived service quality and how it leads to loyalty towards service providers. Finding – Results indicate that the service seeker-service provider relationship, quality of facilities and the interaction with supporting staff have a positive effect on customer perception. Practical implications – Findings help healthcare managers to formulate effective strategies to ensure a better quality of services to the customers. This study helps healthcare managers to build customer loyalty towards healthcare services, thereby attracting and gaining more customers. Originality/value – This paper will help healthcare managers and service providers to analyse customer perceptions and their loyalty towards Indian private healthcare services.